INNOVATION IMPLEMENTATION TECHNOLOGIES IN INTEGRATED MANAGEMENT SYSTEM OF THE ENTERPRISE - E. Hmelchenko (Вестник университета)
In the current conditions of tough competition between producers of goods and services, the problem of introducing innovations, creating new types of products and services, improving the technologies and forms of organization of production becomes paramount.